Energetic Ionospheric Upwelling: A Case Study of Velocity Distribution and Ion Flux Observed by the EISCAT Svalbard Radar - Timothy W David; Chizurumoke M Michael; Tunde D Awoyinka; Abayomi E Ajetunmobi; Adetoro T Talabi (International Journal of Energetica)
When outflow of heavy ions such as O+ occurs, the atmospheres of planets are gradually loss. The ions being depleted in the ionosphere, under favourable conditions, upwell into the underlying magnetosphere and forms a substantial part of plasma in the magnetosphere. The motion of the heavy ions affects the Alfvén speed as a result, alters global magnetospheric dynamics. Joule heating, electron precipitation and other suprathermal energization are part of the mechanisms involved in the outflow process. Seven hundred and sixty two 762 events of periods of noticeable velocity upflow in conjunction with activities in the electron precipitation as well as enhancement in electron and/or ion temperature(s) were observed by the EISCAT Svalbard Radar (ESR) during the 2007 campaign. The 762 events were categorized by velocity strength in a colour coded plots.  A further observation of periods when the ion upward velocity covered a wide range of altitude is examined, and the distribution of the events shows that about 9.2% of the upflow velocity covers a wide range of altitude. Furthermore, analysis shows that the distribution of high velocity events (≥ 200 ms-1), in conjunction with Kp ≥ 4 is peaked around local noon while other upwelling’s of moderate and low velocities with same range of Kp is skewed towards the night-side. Ion upwelling on the other hand, being a function of electron density and the corresponding velocity, shows that events of same velocity range, may belong to different flux regime, and vice versa.